(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
This study examines the impact of laboratory-based teaching methods on female students’ attitudes and academic performance in Chemistry in Kontagora, Niger State, Nigeria. Utilizing a quasi-experimental design, the study involved two groups: an experimental group receiving laboratory-based instruction and a control group taught via traditional methods. Data were collected through pre- and post-tests on academic performance and attitude surveys. Instruments used included the Chemistry Performance Test (CPT) and the Students’ Attitude to Chemistry Laboratory Scale (SACLS). Data were analyzed using SPSS with Multivariate Analysis of Covariance (MANCOVA) and independent t-tests. Results indicated significant improvements in both performance and attitudes among students taught with laboratory methods. The study concludes that the laboratory method is an effective instructional strategy and recommends its broader adoption in Chemistry classrooms across Niger State.